Pengaruh Pengaruh Pendidikan Keluarga Terhadap Keluarga Risiko Stunting: Systematic Review: Pengaruh Pendidikan Keluarga Terhadap Keluarga Risiko Stunting: Systematic Review - Ananta, Aris; Brantasari, Mahkamah; Azainil (SISTEMA: Jurnal Pendidikan, 2024)
Stunting prevention in Indonesia is still experiencing challenges, including cases of Low Birth Weight (LBW) which still increased by 0.55% in 2018 to 6.25%, the proportion of complete basic immunization which is still low, namely 57.9% in 2018, mothers and toddlers with the condition of energy deficiency who have not received PMT is still relatively high (74.8% and 59%), and anemia in pregnant women (48.9%) in 2018. Problems that often arise in the family environment are related to the attitudes and knowledge of parents in educating their children. The level of education can influence the incidence of stunting but does not occur significantly, this may be influenced by each parent's ability to access information. This research uses a systematic review method, which is a strong approach to compiling and synthesizing evidence from various existing studies on certain topics to find out the complex causes of stunting in a family. Keywords: stunting, parental education level, stunting information.